Accurate quantification of CXCR4-using HIV-1 variants by Illumina deep-sequencing. (23rd October 2018) - Raymond, Stéphanie; Delaugerre, Constance; Nicot, Florence; Assoumou, Lambert; Lancar, Rémi; Beniguel, Lydie; Izopet, Jacques
Abstract : N/A: Next-generation sequencing is a sensitive method for determining HIV-1 tropism but there is a lack of data on the quantification of X4 variants. We evaluated MiSeq and 454 GS-Junior platforms for determining HIV-1 tropism and for quantifying X4 variants. Both platforms were 93% concordant for determining HIV-1 tropism and correlated well for determining the proportion of X4 variants (Spearman correlation, ρ  = 0.748; P  < 0.0001). MiSeq Illumina sequencing seems to be well adapted for characterizing X4-containing samples.